Regional Development: New Challenges for Engineering Education (SYNERGY-2021 Conference Results Review) - V. V. Kondratyev; M. F. Galikhanov; F. T. Shageeva; P. N. Osipov; L. V. Ovsienko (Высшее образование в России)
The article summarizes the results of the plenary session of the international network conference “Regional development: new challenges for engineering education – SYNERGY-2021”, held at Kazan National Research Technological University from October 19 to 20, 2021. The forum which brought together representatives of universities and industrial enterprises of Russia and abroad was devoted to the issue of training engineers for the petrochemical industry. Among the participants were representatives of international societies for engineering education, ten national research universities and seven supporting universities of PJSC Gazprom, state authorities and industrial enterprises of Tatarstan. It was possible to observe the work of the plenary session in real time via the Internet in all the supporting universities of Gazprom. The event was organized by the Ministry of Science and Higher Education of the Russian Federation, the International Society for Engineering Pedagogy (IGIP), the Association of Engineering Education of Russia (AIOR), as well as the Ministry of Industry and Trade of the Republic of Tatarstan and Kazan National Research Technological University. Gazprom PJSC became the general sponsor. In total, the conference gathered more than 450 participants (380 online and 85 in person) from 40 universities in Russia, the USA, Great Britain, Germany, Portugal, Finland, Poland, Kazakhstan, Belarus, Armenia, Latvia, and Estonia. Representatives of 7 industrial enterprises spoke, 77 reports were made.